2011
DOI: 10.1029/2010ja016232
|View full text |Cite
|
Sign up to set email alerts
|

Resonant scattering of plasma sheet electrons leading to diffuse auroral precipitation: 1. Evaluation for electrostatic electron cyclotron harmonic waves

Abstract: [1] Using statistical wave power spectral profiles obtained from CRRES and the latitudinal distributions of wave propagation modeled by the HOTRAY code, a quantitative analysis has been performed on the scattering of plasma sheet electrons into the diffuse auroral zone by multiband electrostatic electron cyclotron harmonic (ECH) emissions near L = 6 within the 0000-0600 MLT sector. The results show that ECH wave scattering of plasma sheet electrons varies from near the strong diffusion rate (timescale of an ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(185 citation statements)
references
References 60 publications
7
178
0
Order By: Relevance
“…and another one for suprathermal electronsf st =n st exp(−(v 2 + v 2 ⊥ )/v 2 T ,st ), wheren is the density of warm/hot electrons (resonantly interacting with whistler waves) normalized to the background electron density, v T = 2T /m e , v T ⊥ = √ 2T ⊥ /m e are thermal electron velocities (parallel and perpendicular to the background magnetic field),n st is the density of suprathermal electrons (responsible for wave damping) normalized to the background electron density, and v T ,st is the thermal velocity of suprathermal electrons (the corresponding temperature is taken as ∼ 300 eV, in rough agreement with various satellite in situ measurements at L ∼ 5-6-e.g., see , Ni et al 2011c, Fu et al 2014b. For this form of the velocity distribution function, Eq.…”
Section: Whistler-mode Wave Growth/damping Rates For Maxwellian Electmentioning
confidence: 97%
“…and another one for suprathermal electronsf st =n st exp(−(v 2 + v 2 ⊥ )/v 2 T ,st ), wheren is the density of warm/hot electrons (resonantly interacting with whistler waves) normalized to the background electron density, v T = 2T /m e , v T ⊥ = √ 2T ⊥ /m e are thermal electron velocities (parallel and perpendicular to the background magnetic field),n st is the density of suprathermal electrons (responsible for wave damping) normalized to the background electron density, and v T ,st is the thermal velocity of suprathermal electrons (the corresponding temperature is taken as ∼ 300 eV, in rough agreement with various satellite in situ measurements at L ∼ 5-6-e.g., see , Ni et al 2011c, Fu et al 2014b. For this form of the velocity distribution function, Eq.…”
Section: Whistler-mode Wave Growth/damping Rates For Maxwellian Electmentioning
confidence: 97%
“…The presence of a parallel potential drop (an upward field-aligned current) will block secondaries from escaping the ionosphere. It is also possible that electromagnetic wave activity, specifically upper band chorus [Ni et al, 2011a] and electron cyclotron harmonic (ECH) [Peticolas et al, 2002] waves, in the equatorial magnetosphere could be scattering the secondaries out of the loss cone. In addition, although 10.1002/2015JA021292 there are variations in periodicities between the events, there are no discernible correlations between local time of occurrence and such periodicities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the 427.8 nm emissions excited by the precipitating electrons above a few keV and the 630.0 nm emissions excited by the <500 eV soft electrons mainly from the magnetosheath (e.g., Smith and Lockwood, 1996), the 557.7 nm emissions, the focus of this study, are triggered by the atmospheric precipitation of ≥500 eV to a few keV electrons, which dominantly come from the magnetosphere. For plasma sheet electrons, a number of studies have demonstrated that resonant wave-particle interactions can play an essential role in driving their efficient precipitation loss (e.g., Ni et al, 2008Ni et al, , 2011aSu et al, 2009;Thorne et al, 2010;Tao et al, 2011). Since moderate dayside chorus is present >10 % of the time and can persist even during periods of low geomagnetic activity (Li et al, 2009), especially at high L-shells where the YRS is located, it is natural to connect the presence of dayside chorus to the occurrence of dayside diffuse aurora.…”
Section: Instrumentation and Observationsmentioning
confidence: 99%
“…Recent comprehensive theoretical and modeling studies in combination with CRRES observations Ni et al, 2011a, b) have revealed that scattering by electromagnetic whistler-mode chorus waves is the dominant cause of the most intense diffuse auroral precipitation on the night-to-dawn side in the inner magnetosphere (L <∼ 8).…”
mentioning
confidence: 99%